Eco-friendly gradient porous poly(3-hydroxybutyrate)/natural fiber aerogels for highly efficient thermo-acoustic insulation - Akhila, N. S.; Shrishti, S. K.; Suresh, Sruthi; Torris, Arun; Gowd, E. Bhoje (ACS Applied Polymer Materials, 2026)
The urgent demand for lightweight thermo-acoustic insulation (TAI) materials in transportation and building infrastructure is constrained by difficulties in synthesis and environmental concerns about nondegradable materials. In this study, a strategy is proposed to create gradient porous, biodegradable, fibrillar aerogels via layer-by-layer casting with poly(3-hydroxybutyrate) (PHB), banana fibers (BF), and cellulose nanofibers (CNFs), followed by unidirectional freezing and freeze-drying. These gradient porous aerogels possess a hierarchical porous structure, ensuring excellent hydrophobicity, mechanical strength, and thermal dimensional stability, and exhibit excellent acoustic insulation performance due to impedance mismatch and pore-neck resonance effects, achieving a noise reduction coefficient (NRC) of 0.60. The gradient-structure-based aerogels also exhibit better thermal insulation performance, with ultralow thermal conductivities as low as 0.03 W/(m & centerdot;K). The flame-retardant properties are significantly enhanced by incorporating Al(OH)3 via a solvent-exchange method, thereby achieving a limiting oxygen index (LOI) of 29.3%. The lightweight, gradient-structure-based, biodegradable aerogels possess excellent thermo-acoustic insulation and flame-retardant properties, thereby offering great promise as sustainable insulation materials for next-generation building infrastructure.
Keywords: acousticinsulation; aerogels; biodegradable; flame retardancy; Hydrophobic; poly(3-hydroxybutyrate); Thermal insulation